Structural stability, mechanical, and optoelectronic properties of A2TlBiI6 (A = Cs and Rb) for energy harvesting: A first principles investigation. (May 2023) - Haq, Anwar ul; Iqbal, Sadia Sagar; Ahmad, Afaq; Ahmad, Tasawer Shahzad; Bakar, Abu; Ramay, Shahid M.
Abstract: Halide double perovskite materials have potential application in renewable energy devices. Herein, the optoelectronic properties and mechanical stability of A2 TlBiI6 (A = Cs and Rb) determined using density functional theory utilizing WIEN2k code have been presented. The traditional and recently modified versions of the tolerance factors have helped identify these compounds as structurally stable, whereas the enthalpy and positive values of the frequency of phonon dispersion indicate the dynamical stability of these perovskite materials. Density of states and band structure calculations indicate that the electronic transition occurs from the top of the valence band [Tl(6p)+Bi(6p)+I(5s)] to the bottom of the conduction band [Tl(6p)+Bi(6p)]. These electronic transitions are responsible for inherently direct band gap at the Γ-point of the first Brillouin zone. The energy band gap calculations for Cs2 TlBiI6 and Rb2 TlBiI6 give direct band gap values of 2.0 and 2.1 eV, respectively. Our results show that Tl–Bi based double perovskites exhibit considerable stability, suitable band gaps, and excellent light absorption. In particular, direct band gap materials are very promising for use in a multi-junction solar cell. We hope that our work will stimulate the interest of experimental and theoretical experts to synthesize new materials for the solar industry. Highlights: Researchers are trying to search for eco-friendly materials for the production of photovoltaic devices. Perovskites are used to fabricate thin film type cells with faster improvement in efficiency from 3% (2009) to 25% (2020). Inorganic halide double perovskites (IOHDPs) emerged as eco-friendly stable halide perovskites.